A walk through life: issues and challenges through the eyes of a muslim woman - Norma Kassim (NK & Associates Kuala Lumpur, 2007)
A Walk Through Life: Issues and Challenges Through the Eyes of a Muslim Woman offers insights into the personal and social experiences of a Muslim woman, addressing identity, faith, and resilience in contemporary society.